Utilisation of Fuzzy Fault Tree Analysis (FFTA) for quantified risk analysis of leakage in abandoned oil and natural-gas wells - Lavasani, Seyed Miri; Ramzali, Nahid; Sabzalipour, Farinaz; Akyüz, Emre (Pergamon-Elsevier Science Ltd, 2015)
It is a fact that a significant number of drilled wells are abandoned each year. Abandoned wells, those that have been Permanently Abandoned (PA), might have some risks with disastrous consequences. Moreover, abandoned leaking oil wells and natural-gas wells can cause serious damage to environment. In conventional Fault Tree Analysis (FTA), the failure probabilities of components of a system are treated as exact values in estimating the failure probability of the Top Event (TE). There is always a lack of data for calculating the failure rate of components in the drilling industry. Therefore, fuzzy theory can be used as solution to solve the problem. The aim of this paper is to analyse the leakage through PA oil and natural-gas wells in drilling industry by utilising Fuzzy Fault Tree Analysis (FFTA). As a result, the research has provided theoretical and practical contributions to maritime safety and ocean environmental protection. (C) 2015 Published by Elsevier Ltd.
Keywords: Fuzzy fault tree analysis; Top event; Risk analysis; Oil and natural-gas wells; Off-shore industry